Human capital investment : an international comparison - (:unkn) unknown (My University, 1998)
"Knowledge, skills and competences constitute a vital asset in supporting economic growth and reducing social inequality in OECD countries. This asset, which is often referred to as human capital, has been identified as one key faktor in combating high and persistent unemployment and the problems of low pay and poverty. As we move into "knowledge-based" economies the importance of human capital becomes even more significant than ever. Against a background of tight fiscal constraints in almost all countries, Governments are concerned about the importance of measuring the impact of education and training budgets on economic performance and the welfare of societies. Together with businesses and individuals, public authorities share a common interest in renewing and increasing the skills base of the population and workforce. Moreover, there is an increased awareness of the importance of lifelong learning in a society where economic, social and technological change call for flexibilty, adaptation and learning throughout life. These were some of the principal considerations which prompted Ministers meeting in the Council of the OECD in 1996 to request the OECD to develop an initial set of indicators of human capital investment based on existing data, analyse areas where significant gaps remain in inernationally comparable data, identify the cost of development of data collection for new measures and performance indicators. This report ist a response to that request. Drawing on a range of indicators based on existing data, the report also highlights key policy-related issues such as the important role of both private and public agents in sponsoring and funding learning troughout life, as well as inequality in access to training by different groups. An important conclusion is that it is insufficient to rely upon aggregate measures of the amount of human capital. It is also important to know how human capital is distributed among different groups in the population, as well as how skills and knowledge are employed in everyday life. While the report focuses on information and data from existing sources, it also identifies key areas in which new information about human capital is distributed among different groups in the population, as well as how skills and knowledge are employed in everyday life. While the report focuses on information and data from existing sources, ist also identifies key areas in which new information about human capital investment is needed to guide policy-making. These relate to areas which include workplace learning and skills, as well as the need for measures of a broader range of skills. Der OECD-Bericht über Humankapitalinvestitionen befasst sich mit Bedeutung, Umfang und Messung von Humankapital. Es werden Indikatoren entwickelt, Bereiche analysiert, in deren Lücken an international vergleichbaren Daten bestehen Entwicklungskosten für die Sammlung von Daten für neuere Massnahmen und und Leistungsindikatoren identifiziert. Ausserdem werden entscheidende bildungspolitische Themen wie öffentliche und private Finanzierung des Lernens während der Lebensspanne und mangelnde Chancengleichheit beim Jugendamt zu Aus- und Weiterbildung für verschiedene Gruppen beleuchtet. Auch auf die Verteilung des Humankapitals auf verschiedene Bevölkerungsgruppen und die im Alltagsleben wird eingegangen. (IAB)
Keywords: S 4.3.6 Human Capital; G 1.2.3.1 Potenziale; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; Humankapital; Indikatoren; Bildungsinvestition; Internationaler Vergleich; Bildungsertrag; Qualifikation; Messung; Lebenslanges Lernen; OECD